2014
DOI: 10.1186/1750-1172-9-82
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Niemann-Pick disease type C with 7-ketocholesterol screening followed by NPC1/NPC2 gene mutation confirmation in Chinese patients

Abstract: BackgroundIt has been reported that oxidation product of cholesterol, 7-ketocholesterol, increases in plasma of patients with NP-C. Previously, we established a rapid test to determine the plasma 7-ketocholesterol level and found it elevated significantly in patients with acid sphingomyelinase deficient NPD and NP-C disease.MethodsIndividuals randomly referred to our outpatient clinics in the past two years for hepatosplenomegaly or isolated splenomegaly, who have been excluded as acid sphingomyelinase deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
(61 reference statements)
3
24
0
Order By: Relevance
“…In this context, previous studies implicating oxidative stress in NPC disease pathogenesis raised the possibility that non-enzymatic formation of cholesterol oxidation products could serve as disease biomarkers [3]. Since Porter et al in 2010 [17] published increased levels of plasma oxysterols in NPC1 patients, which were also correlated with age of disease onset and disease severity, new methods of measuring these metabolites began to be investigated [13,23,32,33]. Early detection of NPC disease by an oxysterol-based newborn screening test would facilitate diagnosis in presymptomatic NPC subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, previous studies implicating oxidative stress in NPC disease pathogenesis raised the possibility that non-enzymatic formation of cholesterol oxidation products could serve as disease biomarkers [3]. Since Porter et al in 2010 [17] published increased levels of plasma oxysterols in NPC1 patients, which were also correlated with age of disease onset and disease severity, new methods of measuring these metabolites began to be investigated [13,23,32,33]. Early detection of NPC disease by an oxysterol-based newborn screening test would facilitate diagnosis in presymptomatic NPC subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is desirable to have the concurrence of other methods or other biomarkers to help the diagnosis of this disease. Recent studies have shown that plasma CT and 7-KC could be potential biomarkers for the diagnosis of NPC patients (8)(9)(10)(11)(12)(13). We aimed to determine the sensitivity and specifi city of these biomarkers for the diagnosis of NPC compared with patients suffering from other lysosomal, peroxisomal, or sterol disorders, or other patients with hepatic or neurological alterations, as well as patients with familial hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the NPC murine model, an increase of two oxysterols, cholestane-3 b ,5 a ,6 b -triol (CT) and 7-ketocholesterol (7-KC), has been observed ( 8 ). This evidence was later confi rmed in NPC patients (8)(9)(10)(11)(12)(13), showing a correlation between the oxysterol profi le and the age of onset and severity of the disease ( 8,14 ). Moreover, CT specifi cally has been found to be increased in NPC disease compared with other lysosomal and neurodegenerative diseases ( 8 ).…”
mentioning
confidence: 96%
“…Pre-specified populations with sufficient suspicion of NP-C would include infants with neonatal cholestatic liver disease [2], patients with hepatosplenomegaly [31], the intellectually disabled [32] and adults with neurological and psychiatric symptoms [4]. Together with differential clinical diagnosis, the standard enzymatic tests for Gaucher and NP-A/ B could also be used as an alternative to sequencing to differentiate these disorders from NP-C in patients with elevated plasma SPC and GlcSph.…”
Section: Glucosylsphingosinementioning
confidence: 99%